Peningkatan Pengetahuan Mengenai Pembuatan MP-ASI Bagi Ibu-ibu Anggota Komunitas MP-ASI Homemade (KMHM) Jember - Galih Purnasari; Yoswenita Susindra; Puspito Arum (Journal of Community Development, 2022)
Stunting and underweight are nutritional problems in toddlers that are often experienced by Indonesian toddlers to date. Inappropriate feeding practices are the main cause of early nutritional problems in infants and toddlers. Fulfillment of nutrition in a child begins with exclusive breastfeeding for 6 months and continues with complementary feeding (MP-ASI). Ignorance and/or inability to prepare complementary foods that meet nutritional needs appropriately and hygienically is one of the causes of nutritional problems in toddlers. Education about infant and child feeding needs to be given as an effort to prevent nutritional problems. The purpose of this community service activity is to increase the knowledge of mothers under five about producing of MP-ASI for mothers who are members of the Homemade MP-ASI Community (KMHM). This training as an education in community service includes webinars via Zoom. The results of the training showed that there was an increase of participants’ knowledge. Based on the results of Wilcoxon test, it showed that there was an increase in the knowledge of mothers under five about processing and preparing MP-ASI properly.